Morphological, mechanical and thermal properties of nylon 6/ABS blends using glycidyl methacrylate-methyl methacrylate copolymers - Araújo, E. M.; Hage, E.; Carvalho, A. J. F. (Springer Nature, 2005)
Nylon6 is an attractive polymer for engineering applications because it has reactive functionality through amine and carboxyl end groups that are capable of reacting. For this reason, it has been used a lot in polymeric blends. Blends of nylon6/ABS (acrylonitrile-butadiene-styrene) were produced using glycidyl methacrylate-methyl methacrylate (GMA-MMA) copolymers as compatibilizer. The binary blends were immiscible and exhibited poor mechanical properties that stemmed from the unfavorable interactions among their molecular segments. This produced an unstable coarse phase morphology and weak interfaces between the phases in the solid state. The presence of the copolymer in the blends clearly led to a more efficient dispersion of the ABS phase and consequently optimized Izod impact properties. However, the compatibilized blend showed poor toughness at room temperature and failed in a brittle manner at subambient temperatures. © 2005 Springer Science + Business Media, Inc.
Keywords: ABS resins; Acrylics; Amines; Copolymers; Dispersions; Interfaces (materials); Morphology; Polymer blends; Solubility; Engineering applications; Molecular segments; Nylon 6; Reactive functionality; Nylon polymers